2018
DOI: 10.35799/pmj.1.1.2018.19648
|View full text |Cite
|
Sign up to set email alerts
|

UJI AKTIVITAS FAGOSITOSIS MAKROFAG EKSTRAK ETANOL DAUN SUJI (Dracaena angustifolia (Medik.)Roxb. ) SECARA IN VITRO

Abstract: UJI AKTIVITAS FAGOSITOSIS  MAKROFAG  EKSTRAK ETANOL  DAUN SUJI (Dracaena angustifolia (Medik.)Roxb. ) SECARA  IN VITRONestri Handayani 1,2*), Subagus Wahyuono2), Triana Hertiani2), Retno Murwanti2)1)Program Studi Farmasi, FMIPA, Universitas Sebelas Maret Surakarta2)Fakultas Farmasi Universitas Gadjah Mada Yogyakarta*Email : nestri.uns@gmail.com  ABSTRACT Immunomodulatory activity has been carried out on ethanol extract of suji leaf (Dracaena angustifolia (Medik.) Roxb with in vitro macrofag phagocytosis method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
6
0
3
Order By: Relevance
“…Most foreign substances that enter the tissue are eliminated through phagocytosis. Phagocytosis of macrophages is widely used as an immunological measure in assessing the health or function of the body's defense system (Handayani, 2018). Research conducted by Foysal et al (2020) reported that a combination of two or more probiotics, including Lactobacillus species, could improve the performance of the immune system of aquatic hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Most foreign substances that enter the tissue are eliminated through phagocytosis. Phagocytosis of macrophages is widely used as an immunological measure in assessing the health or function of the body's defense system (Handayani, 2018). Research conducted by Foysal et al (2020) reported that a combination of two or more probiotics, including Lactobacillus species, could improve the performance of the immune system of aquatic hosts.…”
Section: Discussionmentioning
confidence: 99%
“…7 Makrofag adalah sel yang berperan penting dalam sistem imunitas tubuh untuk melawan patogen dengan cara fagositosis. 7,8 Fagositosis ini dapat memicu aktivasi makrofag untuk mensintesis berbagai mediator inflamasi, antara lain interleukin 1 (IL-1) dan tumor necrosis factor-α (TNF-α). 8 Mediator-mediator tersebut menjadikan makrofag sebagai pertahanan tubuh yang kuat, tetapi apabila makrofag teraktivasi secara berlebihan justru dapat menyebabkan kerusakan jaringan.…”
Section: Pendahuluanunclassified
“…7,8 Fagositosis ini dapat memicu aktivasi makrofag untuk mensintesis berbagai mediator inflamasi, antara lain interleukin 1 (IL-1) dan tumor necrosis factor-α (TNF-α). 8 Mediator-mediator tersebut menjadikan makrofag sebagai pertahanan tubuh yang kuat, tetapi apabila makrofag teraktivasi secara berlebihan justru dapat menyebabkan kerusakan jaringan. 7 Limfosit merupakan sel inflamasi kronis yang bersifat spesifik sebagai respons imun host terhadap adanya suatu jejas saat terjadi inflamasi yang bersifat kronis.…”
Section: Pendahuluanunclassified
“…Plants that contain metabolite compounds can help the wound healing process (Fernandes, Maharani, Sunarta, & Rayan, 2018;Handayani, Sundu, & Karapa, 2017;Wijonarko, Anies, & Mardiono, 2016). The content of active substances such as flavonoids, saponins, and polyphenols in the kecombrang Sedian leaf extract gel is effective in healing rabbits' cut wounds (Ruslim, Anitasari, Ismail, Oli, & Yani, 2017).…”
Section: Introductionmentioning
confidence: 99%